Insect Biodiversity In Tiger Camp, Lubuk Minturun: Padang, Indonesia - Zulyusri, Zulyusri; Putri, Zulgusma Aulia (Biospecies, 2025)
This study aims to explore insect diversity in the Tiger Camp area, Padang, through the analysis of three main indices: Diversity Index (H'), Dominance Index (D), and Balance Index (E). Data were collected through intensive field surveys, using insecnet (sweep net) and hand shorting insect capture methods. The results of the study obtained 117 individuals, 59 species, 22 families, and 6 orders which showed that the Diversity Index (H') in the Tiger Camp area was 3.79, indicating a high level of species diversity. The Dominance Index (D) value of 0.03 indicates that no species significantly dominated the insect community. The Equilibrium Index (E) of 0.97 indicated a very even distribution of insect individuals among different species. These findings indicate that the insect community at Tiger Camp, Padang, has high diversity and good ecological stability. The high values of diversity and balance, as well as low dominance, indicate that the habitat in this area supports a healthy and sustainable environment for a variety of insect species. This study highlights the importance of natural habitat conservation to maintain biodiversity and ecosystem balance in the area.